1996
DOI: 10.3168/jds.s0022-0302(96)76554-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Selenium and Iodine Supplementation on Growth Rate and on Thyroid and Somatotropic Function in Dairy Calves at Pasture

Abstract: The effects of Se and I supplementation on growth rate and on thyroid and somatotropic function were examined for heifer calves from two herds fed pasture. Supplementation of calves with intraruminal Se pellets increased the basal plasma concentration of 3,5,3'-triiodothyronine and reduced the basal plasma concentration of thyroxine for both herds. For one herd, supplementation with Se increased the triiodothyronine response to challenge with thyrotropin-releasing hormone, increased BW gain, and tended to incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
2
3

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 10 publications
4
42
2
3
Order By: Relevance
“…The difference can be probably explained by an increased activity of iodothyronine deiodinase, which participates in the conversion of T4 into active T3 and which activity is influenced by selenium (Arthur et al, 1990;Larsen and Berry, 1995;Kohrle, 2000). Similar results confirming a positive effect of selenium on T3 concentrations were presented for instance by Wichtel et al (1994) and Awadeh et al (1998), who observed increased T3 concentrations in cows and calves a�er higher selenium intake. The ratio of T3 : T4 calculated in our work (0.039-0.055) is close to the results of the previously mentioned authors (0.023-0.040).…”
Section: Resultssupporting
confidence: 74%
“…The difference can be probably explained by an increased activity of iodothyronine deiodinase, which participates in the conversion of T4 into active T3 and which activity is influenced by selenium (Arthur et al, 1990;Larsen and Berry, 1995;Kohrle, 2000). Similar results confirming a positive effect of selenium on T3 concentrations were presented for instance by Wichtel et al (1994) and Awadeh et al (1998), who observed increased T3 concentrations in cows and calves a�er higher selenium intake. The ratio of T3 : T4 calculated in our work (0.039-0.055) is close to the results of the previously mentioned authors (0.023-0.040).…”
Section: Resultssupporting
confidence: 74%
“…The additive nature of the effects of treatment with Se and I on plasma thyroxine supports the findings for calves (Wichtel et al 1995). The lack of a significant increase in plasma total triiodothyronine concentration in response to Se supplementation disagrees with other reports where supplementary Se increased plasma triiodothyronine in calves (Wichtel et al 1995) and ewes (Donald et al 1993) with Se intakes similar to the goats in the present study. If production responses to Se are mediated via the thyroid axis, changes in the tissue concentration of triiodothyronine, the most active of the thyroid hormones, would be expected.…”
Section: Discussioncontrasting
confidence: 55%
“…However, supplementary Se increased liveweight gain in calves (Wichtel et al 1995) and lambs (Grace et al 1974) grazing pastures containing low concentrations of Se. The tendency for reduced gain in kids supplemented with I in the present study might be because of the increased plasma thyroxine concentration induced by I treatment; in lambs (Coop & Clark 1958) treatment with thyroxine decreased liveweight gain, but increased fleece production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cattle the plasma levels of thyroid hormones may be altered also by other nutrition-and metabolism-related factors, such as selenium and/ or iodine deficiency/supplementation (Wichtel et al, 1996;Awadeh et al, 1998), growth hormone releasing factor and somatotropin administration (Kahl et al, 1995), providing fat-or starchenriched diet (Bunting et al, 1996;Romo et al, 1997;Blum et al, 2000), and feed contaminants, for instance goitrogen chemicals (Gennano-Soffietti et al, 1988;Bernal et al, 1999;rift et al, 1999a, b) and certain ergot like alkaloids produced by endophyte fungi (Neotyphodium coenophialum) of tall fescue (Festuca arundinacea; known as a really existing form on feed contamination only in North America) (Hurley et al, 1981;Browning et al, 1998Browning et al, , 2000.…”
Section: Basic Physiology Nutritional Factors Influencing Thyroid Fumentioning
confidence: 99%